Invasive Infection With emm3/ST15 Streptococcus pyogenes: The First Case Report From China and Complete Genome Analysis - Mu, Xinli; Wang, Yanfei; Sun, Lu; Zhao, Shanshan; Jin, Xi; Zhang, Junli; Yu, Yunsong; Wu, Xueqing (Frontiers in Medicine, 2022)
Streptococcus pyogenes (GAS) may cause severe invasive disease with a high fatality rate, especially M3-type strains, which are less common in China. Here, we report the first emm3/ST15 invasive GAS infection case in China. The patient was diagnosed with severe skin and soft tissue infection (SSTI) and septicaemia caused by one GAS strain. Antibiotic susceptibility tests showed that the isolate was susceptible to all tested drugs. Antimicrobial therapy was then applied, and the patient fully recovered and was discharged from the hospital on Day 43. Whole-genome sequencing was carried out using the Illumina and Oxford Nanopore platforms and revealed this to be the first emm3/ST15-type GAS invasive infection in China. The closely related emm3/ST15-type GAS strains are MGAS315 from the USA and M3-b from Japan. Our finding is a warning that we should pay attention to invasive M3-type GAS infections in China and indicates the global spread of the highly virulent emm3/ST15 GAS strain.